2017
DOI: 10.1002/jcop.21943
|View full text |Cite
|
Sign up to set email alerts
|

Classroom relationships, sense of community, perceptions of justice, and collective efficacy for students’ social well‐being

Abstract: A review of literature suggests a lack of studies analyzing the correlates of school context to social well‐being (SWB). By integrating the perspective of community psychology and social cognition, this study uses structural equation model to examine the effect of classroom climate, classroom sense of community, collective efficacy, and justice beliefs on students SWB. The study involves 390 high school students (58.6% females) between the ages of 13 and 20 years. The results show that classroom relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…Except for a few examples at the microlevel (see Capone, Donizzetti, & Petrillo, 2018;Paloma, García-Ramírez, & Camacho, 2014) it is hard to find quantitative studies in CP, which place social justice in relation to happiness or well-being. As Prilleltensky (2012) has pointed out: "After all, researchers studying subjective well-being rarely if ever invoke justice in their explanations.…”
Section: And the Gross Nationalmentioning
confidence: 99%
“…Except for a few examples at the microlevel (see Capone, Donizzetti, & Petrillo, 2018;Paloma, García-Ramírez, & Camacho, 2014) it is hard to find quantitative studies in CP, which place social justice in relation to happiness or well-being. As Prilleltensky (2012) has pointed out: "After all, researchers studying subjective well-being rarely if ever invoke justice in their explanations.…”
Section: And the Gross Nationalmentioning
confidence: 99%
“…The studies utilizing the Mental Health Continuum (Keyes, 2005) to examine how social well-being relates to PSOC (ISCS for adolescents; Albanesi, Cicognani, & Zani, 2005) among youth and young adults in Italy also found overall positive and significant associations between these variables (Albanesi, Cicognani, & Zani, 2007;Cicognani, Mazzoni, Albanesi, & Zani, 2015). More specifically in the school context, Capone, Donizzetti, and Petrillo (2018) found that PSOC (and all five dimensions included in the PSOC Scale for Adolescents in the Classroom; Petrillo et al, 2016) was significantly and positively associated with social wellbeing. Further,theyfound that social well-being (Cicognani, Pirini, et al, 2008;Keyes, 2005) was significantly and positively associated with school-level PSOC (Petrillo et al, 2016).…”
Section: Adolescent Populationsmentioning
confidence: 99%
“…In the studies encapsulated in the current literature review, both territorial and relational communities are considered, though the studies that include a relational component often frame the referent in a territorial fashion. For example, several studies (e.g., Capone et al, 2018) examine PSOC among students in a classroom or school (territorial), while the measure itself has items concerning relationships with peers (relational).…”
Section: Measurementmentioning
confidence: 99%
“…There are several studies on the effects of collective efficacy and the consequences of group work. For example, Capone, Donizzetti, and Petrillo (2018) showed that collective efficacy can influence student well-being. In a meta-analysis Stajkovic, Lee, and Nyberg (2009) found that collective efficacy was significantly related to group performance.…”
mentioning
confidence: 99%